Semi‐solid 3D printing of mesoporous silica nanoparticle‐incorporated xeno‐free nanomaterial hydrogels for protein delivery - Mahran Alaa; Özliseli Ezgi; Wang Qingbo; Özliseli Ilayda; Bhadane Rajendra; Xu Chunlin; Wang Xiaoju; Rosenholm Jessica M (Wiley, 2025)
Multifunctional biomaterial inks are in high demand for adapting hydrogels in biomedical applications through three-dimensional (3D) printing. Our previously developed xeno-free system consisting of anionic cellulose nanofibers (T-CNF) and methacrylated galactoglucomannan (GGMMA) as a photo(bio)polymer provides high-performance ink fidelity in extrusion-based 3D printing. The fusion between nanoparticles and this biomaterial-ink system is a promising yet challenging avenue worth exploring, due to the colloidal stability of T-CNF being sensitive to electrostatic interactions. Mesoporous silica nanoparticles (MSNs), with their robust ceramic matrix and fine-tunable surface chemistries, are well-established nanocarriers for different biologicals. Here, we fabricated MSNs with different surface modifications resulting in a net surface charge ranging from highly negative to highly positive to develop printable MSNs-laden nanocomposite biomaterial inks. We utilized rheology as a comprehensive tool to address the matrix interactions with differently surface-charged MSNs. Fluorescently labeled bovine serum albumin (FITC-BSA) was used as a model protein for MSN loading, whereby negatively or neutral-charged MSNs were found suitable to formulate FITC-BSA-loaded biomaterial inks of T-CNF/GGMMA. Depending on the particles’ surface charge, FITC-BSA showed different release profiles and preserved its stability after release. Lastly, the proof-of-concept to deliver large-sized biological cargo with MSN-laden nanocomposite biomaterial inks was established via the 3D printing technique.